Direct current and microwave characteristics of sub-micron AlGaN/GaN high-electron-mobility transistors on 8-inch Si(111) substrate - Arulkumaran, Subramaniam (2013)
We report for the first time the DC and microwave characteristics of sub-micron gate (∼0.3 µm) AlGaN/GaN high-electron-mobility transistors (HEMTs) on 8-in. diameter Si(111) substrate. The fabricated sub-micron gate devices on crack-free AlGaN/GaN HEMT structures exhibited good pin.-off characteristics with a maximum drain current density of 853 mA/mm and a maximum extrinsic transconductance of 180 mS/mm. The device exhibited unit current-gain cut-off frequency of 28 GHz, maximum oscillation frequency of 64 GHz and OFF-state breakdown voltage of 60 V. This work demonstrates the feasibility of achieving good performance AlGaN/GaN HEMTs on 8-in. diameter Si(111) for low-cost high-frequency and high-power switching applications.